Carl Schmitt and the Buribunks : technology, law, literature - Tranter, Kieran; Bikundo, Edwin; Schmitt, Carl, 1888-1985. (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"In 1918 a young Carl Schmitt published a short satirical fiction The Buribunks. He imagined a future society of beings who consistently wrote and disseminated their personal diaries. Schmitt would go on to become the infamous philosopher of the exception and for a while the 'Crown Jurist of the Third Reich.' The Buribunks - ironically for beings that lived only for self-memorialisation - has been mostly lost to history. However, the digital with its emphasis on the informatic traces generated by human doing and the continual interest in Schmitt's work to explain and criticise contemporary constellations of power, suggest that The Buribunks is a text whose epoch has come. This volume includes the first full translation into English of The Buribunks and a selection of critical essays on the text, its meanings in the digital present, its playing with and criticism of the literary form and its place within Schmitt's life and work. The Buribunks and the essays provide a complex, critical and provocative invitation to reimagine the relations between the human and their imprint and legacy within archives and repositories. There is a fundamental exploration of what it means to be a being intensely aware that it means to be 'writing itself.' This is not just a volume for critical lawyers, literary scholars and the Schmitt literati. It is a volume that challenges a broad range of disciplines, from philosophy to critical data studies, to reflect on the digital present and its assembled and curated beings. It is a volume that provides a set of fantastically located concepts, images and histories that traverse ideas and practices, play and politics, power and possibility"--
The Buribunks as law, technology and literature / Kieran Tranter and Edwin Bikundo -- The Buribunks : an essay on the philosophy of history / Carl Schmitt, translated from the German by Gert Reifarth and Laura Petersen -- Behind the words of Die Buribunken : translators' comments / Laura Petersen and Gert Reifarth -- The Buribunks, post-truth and a tentative cartography of informational existence / Kieran Tranter -- The theological-bureaucratic science fiction of Philip K. Dick and Carl Schmitt : an economic theology of omniscience in the Buribunks / Timothy D. Peters -- Inauthentic temporality and the age of hyperburibunkism / Richard Polt -- Megarianism, emancipation and the (im)potentiality of political ontology : a commentary on freedom in Schmitt's dystopia / Michael P.A. Murphy -- The challenges of anti-intellectual parody / Karen Petroski -- 'Quantity turns into quality' : breathing life into dead scholasticism / Francine Rochford -- On writing. Under control. The Buribunks and the autographic society of control / Vittorio Lubrano -- Modernist life-writing and early cinema in Carl Schmitt's the Buribunks / Joseph Owen -- 'Die Buribunken' -- a pastiche : a mechanised modernity failing Hegel and Kierkegaard / Nour Benghellab -- Sola scriptura : doubling of life and critique of modernity in the Buribunks / Ernesto C. Sferrazza Papa -- Schmitt's Roman links in the Buribunks : enriching the satire / Karen Schultz -- Mephistophelean irony in Carl Schmitt's political romanticism, the Buribunks and ex captivitate Salus / Desmond Manderson and Edwin Bikundo -- Imagined facts, actual enemies : the Buribunks and the political / Attila Gyulai -- Between the Buribunks and the Christian Epimetheus / Fabrizio Grasso and Matteo Negro, translated by Carla Biondi -- Schmitt's life within the academy since 2001 / Lachlan Robb, Charles Lawson, Catherine Pickering and Edwin Bikundo.
Keywords: Schmitt, Carl, -- 1888-1985.; LAW / General; LAW / Jurisprudence; LAW / Legal History